2017
DOI: 10.1111/jdi.12782
|View full text |Cite
|
Sign up to set email alerts
|

Lower mean blood glucose during short‐term intensive insulin therapy is associated with long‐term glycemic remission in patients with newly diagnosed type 2 diabetes: Evidence‐based recommendations for standardization

Abstract: Aims/IntroductionOptimal glycemic targets during short‐term intensive insulin therapy in patients with newly diagnosed type 2 diabetes are not standardized. The present study was carried out to determine the optimal glycemic targets during therapy by analyzing the impacts of glucose levels on therapeutic outcomes.Materials and MethodsA total of 95 individuals with newly diagnosed type 2 diabetes were enrolled. Short‐term intensive insulin therapy was carried out using an insulin pump to achieve and maintain gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
2
16
1
Order By: Relevance
“…Whereas in our previous study, we did not found differences of hypoglycemia between patients in the remission group and those in the nonremission group [23]. The reason was that in our previous studies, hypoglycemia was not analyzed by subgroups.…”
contrasting
confidence: 69%
“…Whereas in our previous study, we did not found differences of hypoglycemia between patients in the remission group and those in the nonremission group [23]. The reason was that in our previous studies, hypoglycemia was not analyzed by subgroups.…”
contrasting
confidence: 69%
“…42 In other trials, a run-in period before starting CSII was performed as well; however, the duration of such periods was highly variable. 16,26,29,41,49,53 In most trials initiating CSII, a basal insulin delivery of 40%-60% of the total daily insulin dose was chosen. 26,27,29,47,56 In some studies, patients stopped previous antidiabetic therapy options when CSII therapy was initiated, 31,33,40,52 whereas others used previous therapy options like oral antidiabetic drugs additionally.…”
Section: Clinical Evidence For Csii In Patients With T2dmmentioning
confidence: 99%
“…Short-term (two to four week) intensive insulin therapy (SIIT) administered early in the course of T2DM acutely improves beta cell function by eliminating glucotoxicity, lipo-toxicity and insulin resistance [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Long-term intensive insulin therapy (LIIT) was used to compensate defective insulin to make physiological form of insulin secretion in the irreversible component of beta cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is possible that stepwise addition of insulin leads to the reduction of hyperglucagonaemia.The evidence of this treatment has been presented to prove benefits in the treatment of T2DM. However, in most SIIT studies, after SIIT they did not use any anti-diabetic agents and evaluated the duration of glycaemic remission [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . As the results, glycaemic remission was temporary, especially when beta-cell function was markedly deteriorated after SIIT.…”
mentioning
confidence: 99%